2019
DOI: 10.21873/anticanres.13844
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Melanoma in African American Patients in the United States

Abstract: Background/Aim: To characterize the demographics, tumor staging and treatment of African American (AA) patients diagnosed with melanoma in the United States. Patients and Methods: The National Cancer Database was used to extrapolate data from patients with melanoma between January 1, 2004, and December 31, 2015. The patients were then further divided based on ethnicity (AAs vs. Caucasians) to compare patient efficacy of treatment. Results: The mean time for AA patients to receive treatment was 20.37 days compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 6 publications
0
22
1
1
Order By: Relevance
“…The signs and symptoms that encouraged a fast consultation of a healthcare professional were the late ones, such as bleeding, whereas observing the standard ABCDE signs led to delay in seeking medical attention. 30,31,[48][49][50][51][52][53] Boriani et al 32 showed that higher aggressiveness of ALM is due to the diagnostic delay and the more advanced thickness at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signs and symptoms that encouraged a fast consultation of a healthcare professional were the late ones, such as bleeding, whereas observing the standard ABCDE signs led to delay in seeking medical attention. 30,31,[48][49][50][51][52][53] Boriani et al 32 showed that higher aggressiveness of ALM is due to the diagnostic delay and the more advanced thickness at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Substantially, the studies of Richards et al 28,29 found that despite the existence of media operation to promote prevention, 25% of the patients believed that removing a tumor was dangerous, only 24.8% were conscious about the gravity of melanoma, and others just assumed that a lesion could not be malignant if asymptomatic. The signs and symptoms that encouraged a fast consultation of a healthcare professional were the late ones, such as bleeding, whereas observing the standard ABCDE signs led to delay in seeking medical attention 30,31,48‐53 …”
Section: Discussionmentioning
confidence: 99%
“…Importante mencionar que 136 (45,6%) indivíduos estudados declararam-se brancos, seguidos de 96 (32,2%) pardos e 54 (18,1%) declararam-se negros. Sabidamente indivíduos com menor concentração de melanina apresentam uma maior susceptibilidade para o desenvolvimento de cânceres e tumores de pele, especialmente o melanoma (BOCZAR et al, 2019;DE MELO et al, 2018;MAHENDRARAJ et al, 2017). A população do nosso estudo é predominantemente jovem e é importante mencionar que dentre os cânceres mais frequentes em adultos jovens, o melanoma é o segundo mais frequente (BARR et al,2006).…”
Section: Discussionunclassified
“…Then, when acral lentiginous melanoma is accurately diagnosed, the prognosis is often poor, with a 5-year survival rate of less than 50% in Black individuals (Davis et al, 2021). Melanoma is often overlooked in Black individuals because of misinformation regarding risk, location, and the difficulty in differentiating melanoma from the patients' natural skin color (Boczar et al, 2019). Furthermore, patients' lack of awareness regarding the risk of skin cancer for Black individuals often delays treatment, resulting in an increased likelihood of death when diagnosed (Hall & Rapini, 2020).…”
Section: Melanoma Risk: What Risk?mentioning
confidence: 99%